2015
DOI: 10.1089/dia.2014.0305
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Assessment of Artificial Pancreas (AP): Commentary and Review of Existing Measures and Their Applicability in AP Research

Abstract: A better understanding of the psychosocial side of AP systems and the extent to which human factors play a role in the uptake and efficient use of these systems will ultimately lead to the most benefit for people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…7 The study showed one of these factors that may play an important role in consistent use of CGM, as the perception of Information Overload had a relevant negative effect on all key variables of TAM-CGM. Reduced complexity in the presentation of data may therefore facilitate CGM usability for some patients and thus improve user experience, possibly increasing adherence.…”
Section: Discussionmentioning
confidence: 87%
“…7 The study showed one of these factors that may play an important role in consistent use of CGM, as the perception of Information Overload had a relevant negative effect on all key variables of TAM-CGM. Reduced complexity in the presentation of data may therefore facilitate CGM usability for some patients and thus improve user experience, possibly increasing adherence.…”
Section: Discussionmentioning
confidence: 87%
“…As medical devices like the AP increase in complexity to provide patients with personalized treatment, their number of loopholes and vulnerabilities also increase [23, 45]. For example, the dual-hormone AP includes an additional infusion system for glucagon and promises to further reduce hypoglycaemic events in comparison to single-hormone systems [21, 46], but the addition of glucagon may amplify security concerns.…”
Section: Domains Of Ethical Issuesmentioning
confidence: 99%
“…In a study exploring adolescent and parent perceptions of the AP following a three-week trial at home, participants reported feeling greater assurance in their ability to manage their T1D, as well as a sense of safety and peacefulness [22]. In two other studies, participants reported similar psychosocial benefits, in addition to improved daily functioning, sleep, and overall quality of life, most likely due to a relief from some key components of T1D care [23, 24]. In return, an AP user must be willing to wear at all times all the pieces of the AP and still needs to rotate the sensor and infusion sites [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conventional endpoints such as glycated hemoglobin, quality of life is to be included to assess burden of disease management and hypoglycemia. A concert effort is underway to develop measures that more adequately capture the role of human and psychological factors play in the uptake and efficient use of closed-loop systems [76,77]. …”
Section: Expert Opinionmentioning
confidence: 99%